Taxonomic status of the Guadalupe Darter, Percina apristis (Teleostei: Percidae) - Robins, Robert H.; Page, Lawrence M. (Zootaxa, 2007)
Percina sciera apristis (Hubbs & Hubbs) was described as a subspecies based on the hypothesis that the population in the Guadalupe River system was morphologically distinct from other populations and that populations geographically closest to the Guadalupe River were intergrades between P. s. sciera and P. s. apristis. Our data confirm the decision to recognize the population in the Guadalupe River as taxonomically distinct; however, western Gulf populations closest to the Guadalupe River do not show a consistent pattern of intermediacy in meristic variables. The Guadalupe population has extreme numbers of preopercular serrae, pored lateral-line scales, modified scales, caudal-peduncle scales, and anal rays. The most extreme trait is the number of preopercular serrae; 95% of individuals from the Guadalupe, but only 6% from other western Gulf drainages, have 0–3 serrae. Sixty-eight percent of Guadalupe individuals, but only 4% from elsewhere, have no serrae. These extreme values demonstrate that the Guadalupe population is genetically isolated and diagnosable as Percina apristis (Hubbs & Hubbs), the Guadalupe Darter.